Evaluation Model of Front End System Implementation of Bank XYZ’s from Customer Side - Sardjono Wahyu; Roifayusyar; Johan (E3S Web of Conferences, 2023)
Information Systems is used by banking companies to process and store financial data and transactions made by customers. The company strives to continuously improve its technological innovations in order to support internal business processes. With the implementation of information technology to contribute to the acceleration of internal business processes that are more efficient and effective internally, it is expected that companies can compete to be more competitive. The purpose of this study is to determine the main factors of the implementation of the existing front end system at bank XYZ, so that further models can be made that can be used to evaluate the performance of the system. This research method is carried out by collecting data from respondents or customers who are directly affected by the service from this front end system, then observations are made using the factor analysis method. The results of this study found that there were new factors formed by the presence of a number of clustered indicators which could then be represented as new factors that reflected the expectations of respondents in particular and bank customers in general. The conclusion obtained is that there are new factors formed: Automation, Information. Management Information Systems, Business Process, and Performance.